A Shared Mechanism of Linguistic, Cultural, and Bodily Relativity. Issue 3 (26th July 2016) - Casasanto, Daniel
Abstract : What's special about the way language influences thought? In some cases, the answer may be: nothing at all. Language influences nonlinguistic cognition via numerous mechanisms. Other forms of experience can also influence our thinking via some of the same mechanisms. This article illustrates how separable streams of linguistic, cultural, and bodily experience can influence the way people think, feel, and make decisions by strengthening some implicit associations in long‐term memory while weakening others. As a result, people with different experiences think differently, in predictable ways. Distinct kinds of physical and social experiences can shape our minds via similar processes, suggesting continuity between different facets of experiential relativity: linguistic relativity, cultural relativity, and bodily relativity.